Pengaruh Digital Marketing dan Customer Relationship Marketing terhadap Loyalitas Konsumen - Satriana, Wulan; Kusnara, Hasti Pramesti (Ma'soem University, 2025)
This study aims to evaluate the extent to which digital marketing and customer relationship marketing influence consumer loyalty at PT. Muawanah Al-Ma’soem. The research employed a quantitative associative approach, with data collected through questionnaires The data testing tools used in this study consist of validity test, reliability test, and normality test. Furthermore, hypothesis testing is carried out through multiple correlation analysis and multiple regression analysis. The sample consisted of 68 respondents out of a total population of 208 individuals. The analysis results show that digital marketing has a significant impact on consumer loyalty, with a t-value of 21.217, which is greater than the critical t-table value of 1.668, and a significance level of 0.000. Likewise, customer relationship marketing also demonstrates a significant influence, with a t-value of 15.795 and a significance level below 0.001. Simultaneously, both variables significantly affect consumer loyalty, as evidenced by the F-test result of 272.312, exceeding the F-table value of 3.138 with a significance level below 0.001. The combined coefficient of determination of 89.3% indicates that the integration of digital marketing and customer relationship marketing strategies plays a crucial role in building consumer loyalty.